A Communication Literacy Study of The Indonesian Ulema Council's Fatwa on Plastic Surgery - Nisfatul Lailiyah; Ikhfa Fauziyatul Maula; Faida Hapsari; Dwi Mujaharoh; Annisatul Karimah; Ahya Adi Septiansyah; Cipto Leksono; Annisa Cikal Nusantara (International Tatho Academics, 2025)
This study aims to identify and explore the function of mass communication in the 2020 fatwa of the Indonesian Ulema Council (MUI) on plastic surgery. This research uses a qualitative method with a literature study approach to analyze the law of plastic surgery according to the 2020 MUI Fatwa. Data were collected through documentation and analyzed through data reduction, presentation, and verification. The findings of this study show that communication functions as social surveillance, mass communication functions as social correlation, and communication functions as social transmission. The theoretical implications of this study regarding mass media function to strengthen religious authority by interpreting fatwas widely to the audience, reconciling social norms and religious understanding. The limitations of this study have not identified the effectiveness of public understanding of the laws of plastic surgery.